Hadith #6443 - Sahih Muslim - Imran al-Barqy عمران البارقي (Sahih Muslim)
I perceive as if I am looking towards that dromedary, and in the hadith transmitted on the authority of Thaqafi (the words are):” Unload it and make its back bare for it is accursed.”
Grade: Sahih